Evaluation of Carboxymethyl Chitosan–Genipin Hydrogels as Reservoir Systems for Suramin Delivery in Epithelial Tissues - David Encinas-Basurto; Victor H. Ruiz; Rick G. Schnellmann; Heidi M. Mansour (Gels)
Hydrogels (HDs) offer a promising platform for localized and sustained drug delivery. In this study, carboxymethyl chitosan (CMC)—based hydrogels were crosslinked with genipin and evaluated for the controlled release and tissue retention of suramin, a polyanionic drug with anti-inflammatory and antifibrotic properties. The influence of crosslinking density (1%, 3%, and 5%) on drug release, permeation kinetics, and retention was investigated using in vitro synthetic membranes and reconstructed human epithelial tissue models. The 1% genipin HD exhibited the highest cumulative release and drug retention (48.8 ± 6.8 μg/cm2 in synthetic membranes; 24.06 ± 7.33 μg/cm2 in epithelial models), along with a sustained release profile governed by first-order and Fickian diffusion kinetics. Notably, the 1% crosslinked formulation also demonstrated enhanced transmembrane flux (>140 μg/cm2/h after six hours), suggesting that lower crosslinking density favors both diffusional mobility and depot functionality. In contrast, free suramin solution displayed limited tissue interaction and minimal permeation, highlighting the role of the hydrogel matrix in regulating local bioavailability. These findings demonstrate that CMC–genipin HD can closely modulate drug delivery kinetics through crosslinking density, offering a biocompatible strategy for localized treatment of ulcerated epithelial conditions such as oral mucositis or chronic wounds. Diffusion models included a synthetic multilayer membrane (Strat-M®) and a reconstructed human epidermis (EpiDerm™) to simulate skin-like barrier properties.